Successful Treatment of Fungal Dermatitis in a Bottlenose Dolphin (Tursiops truncatus) - Takashi Kamio; Honoka Nojo; Rui Kano; Mami Murakami; Yukako Odani; Koji Kanda; Tomoko Mori; Yuichiro Akune; Masanori Kurita; Ayaka Okada; Yasuo Inoshima (Microorganisms)
In recent decades, many fungi have emerged as major causes of disease in marine mammals. This study reports on the detection of filamentous fungi in the subcutaneous tissue and wound surface on the tail fin of a managed bottlenose dolphin (Tursiops truncatus) emaciated due to severe digestive problems. Immunosuppression by chronic diseases and starvation decreased resistance against opportunistic infections. Sequencing analysis revealed that the fungi on the wound surface were Fusarium oxysporum, and antifungal susceptibility testing was performed. In the subcutaneous tissue, dematiaceous fungi were identified using histopathological examination. Combination antifungal treatment with voriconazole and terbinafine and surgical resection were performed, in addition to daily debridement with polyaminopropyl biguanide (PHMB) and betaine. Hematological examination revealed a reduction in inflammatory markers after antifungal treatment and surgical resection of necrotic tissue on the edge of the tail fin. The co-administration of synergistic agents voriconazole and terbinafine, in conjunction with surgical debridement, successfully eliminated pheohyphomycosis and fusariomycosis in the bottlenose dolphin. Wound healing was achieved using systematic antifungals and daily debridement with PHMB and betaine. This is the first report of successful treatment of pheohyphomycosis and fusariomycosis in a bottlenose dolphin using voriconazole and terbinafine combination therapy and surgical resection.